Study of gamma field induced degradation of green GaP light diode electroluminescence characteristics - Kanevsky, S.O.; Litovchenko, P.G.; Opilat, V.Ja.; Tartachnyk, V.P.; Pinkovs'ka, M.B.; Shakhov, O.P.; Shapar, V.M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
Optical and electrical properties of green GaP light diode irradiated by gammairradiation have been studied. Long-lasting relaxation processes on electroluminescence curve of diodes had been observed which one could connect with dark line defects DLD and dark spot defects DSD. Fine structure of negative differential resistance (NDR) region has appeared in I(V)-characteristics at low temperatures (77-110K). Gamma-ray irradiation leads to the broadening of I(V)-curve where oscillations occur. The same action is observed in I(V)- characteristics treated by ultrasonic. Current oscillations are connected with deep recombination centers in depleted region of GaP light diodes. As these levels are located far enough from p-n junction no one can observe them in TLDS spectra.The much greater voltage oscillation amplitude in the NDR region of I(V)- green diode characteristics comparing with red diodes may be bound with their lower defect level.